A stress-response-related inter-compartmental signalling pathway regulates embryonic cuticle integrity in Arabidopsis. - Audrey Creff; Lysiane Brocard; Jérôme Joubès; Ludivine Taconnat; Nicolas M Doll; Anne-Charlotte Marsollier; Stéphanie Pascal; Roberta Galletti; Sophy Boeuf; Steven Moussu; Thomas Widiez; Frédéric Domergue; et al. (PLoS Genetics, 2019)
The embryonic cuticle is necessary for normal seed development and seedling establishment in Arabidopsis. Although mutants with defective embryonic cuticles have been identified, neither the deposition of cuticle material, nor its regulation, has been described during embryogenesis. Here we use electron microscopy, cuticle staining and permeability assays to show that cuticle deposition initiates de novo in patches on globular embryos. By combining these techniques with genetics and gene expression analysis, we show that successful patch coalescence to form a continuous cuticle requires a signalling involving the endosperm-specific subtilisin protease ALE1 and the receptor kinases GSO1 and GSO2, which are expressed in the developing embryonic epidermis. Transcriptome analysis shows that this pathway regulates stress-related gene expression in seeds. Consistent with these findings we show genetically, and through activity analysis, that the stress-associated MPK6 protein acts downstream of GSO1 and GSO2 in the developing embryo. We propose that a stress-related signalling pathway has been hijacked in some angiosperm seeds through the recruitment of endosperm-specific components. Our work reveals the presence of an inter-compartmental dialogue between the endosperm and embryo that ensures the formation of an intact and functional cuticle around the developing embryo through an "auto-immune" type interaction.